2017
DOI: 10.1177/1053825917738269
|View full text |Cite
|
Sign up to set email alerts
|

Learning Technology Integration From a Service-Learning Project: Connecting Preservice Teachers to Real-World Problems

Abstract: Background: Stand-alone educational technology courses have long faced the challenge of connecting preservice teachers to real-world problems of using technology for teaching and learning. Although many studies investigated the benefits of service-learning in teacher education, few were conducted in stand-alone educational technology courses. Purpose: This article reported the benefits and difficulties of a service-learning project that connected preservice teachers with authentic technology integration proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
0
11
0
7
Order By: Relevance
“…A study about students' critical reflection [16], a comparison between online and traditional service learning [14] and success factors of e-Service Learning [3] resulted in one each. -Lawler [3] Case Study Garca-Gutierrez et al [4] -Yusof [5] Mixed Methods Griffin [6] -Nielsen [7] -Shah [8] Case Study Howlett [9] Mixed Methods Helms [10] Saitta [11] Case Study Jia [12] Case Study Gasper-Hulvat [13] -McGorry [14] -Marcus [15] Action research Guthrie and McCracken [16] -Guthrie and McCracken [17] Qualitative Method Salam [18] -Chen [19] -Fry [20] -Ruso [21] Mixed Methods Harris [22] -…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study about students' critical reflection [16], a comparison between online and traditional service learning [14] and success factors of e-Service Learning [3] resulted in one each. -Lawler [3] Case Study Garca-Gutierrez et al [4] -Yusof [5] Mixed Methods Griffin [6] -Nielsen [7] -Shah [8] Case Study Howlett [9] Mixed Methods Helms [10] Saitta [11] Case Study Jia [12] Case Study Gasper-Hulvat [13] -McGorry [14] -Marcus [15] Action research Guthrie and McCracken [16] -Guthrie and McCracken [17] Qualitative Method Salam [18] -Chen [19] -Fry [20] -Ruso [21] Mixed Methods Harris [22] -…”
Section: Resultsmentioning
confidence: 99%
“…Although it is reported that service learning with technology integration had many benefits, Jia et al [12] explores few challenges that happened among preservice teachers such as limited communication with classroom teachers, conflict between classroom teacher expectations and project requirements, inadequate project orientation and instructor support. Either way, Service Learning can create an authentic learning experience among students that connect technology integration with teaching content provided that instructors support students with project orientation and valuable feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Since some of the teachers went through their programs more recently, newer technologies and more readily accessible internet resources would be available, which could mean other factors are at play. This could suggest that technology integration courses need to either model more examples of technology integration for future art teachers, bring in specific examples of how local art teachers are using technology in their classrooms ( Donovan and Green, 2009 ), a specific technology integration course solely for art teachers could be implemented to allow for greater focus on art classroom applications, provide service-learning opportunities ( Jia et al., 2017 ), and/or more modeling may be necessary within art and art education courses to help future art teachers to see more examples and have their entrenched beliefs about the use of technology in the art classroom challenged ( Ertmer and Ottenbreit-Leftwich, 2010 ; Marner and Örtegren, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of teacher education programs prepare pre-service teachers to integrate technology into their future classrooms and teaching by requiring them to complete a minimum of one technology integration course ( Gronseth et al., 2010 ; Jia et al., 2017 ; Kleiner et al., 2007 ; Lambert and Gong, 2010 ). Even though a single technology integration course remains the practice for most teacher education programs, the composition of these courses can vary as they are often a place for curricular experimentation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have been various studies on technology integration [3,[6][7][8]. Lin and Chang [9] focused their research on developing physical activity in children with disabilities using MMK.…”
Section: Introductionmentioning
confidence: 99%